Evaluating Public Procurement's Challenges in Nigeria's Construction Industry - Boniface, Nancy Amarachi; Nnadi, Ezekiel; Eze, Val Hyginus Udoka (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The article explores the challenges faced by public project management in Nigeria, focusing on the procurement process and its potential improvements. The research used a survey and descriptive design, collecting data from 125 procurement offices and federal Ministry of Works professionals. The study found that poor risk management, dark purchasing, corruption, and lack of transparency were the top issues, with a mean score of 4.96. The study also found that the procurement process and industry, economy, and project quality had a joint influence on the dependent variables. The study rejected the null hypothesis, stating that the procurement process significantly impacts the industry, economy, and project quality in Nigeria. The research recommends implementing measures to improve the procurement process and punishing offenders to reduce fraud. The study concludes that the procurement process in Nigeria significantly impacts the industry, economy, and project quality.